Potential vorticity and mixing in the south polar vortex during spring - Hartmann, D. L.; Chan, K. R.; Loewenstein, M.; Podolske, J. R.; Strahan, S. E.; Gary, B. L.; Schoeberl, M. R.; Newman, P. A.; Martin, R. L. (1989)
Fluid dynamic aspects of the Antarctic ozone hole phenomena are studied. Data collected by the ER-2 aircraft as part of the Airborne Antarctic Ozone Experiment (AAOE) are used to calculate the potential vorticity distribution on potential temperature surfaces. Most of the ER-2 flights show a monotonic decrease in potential vorticity and nitrous oxide toward the pole on isentropic surfaces.